(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, it is deeply important to analyze and generalize the results obtained in the process of improving the system of developing knowledge about the history of Uzbek music, conduct experimental work, and develop a methodology for determining the level of effectiveness of future music education teachers. analyzed.